Solubility and Dissolution Enhancement of Lornoxicam by Surface Solid Dispersion - Riyam Sadiq Jafer; Hanan Jalal Kassab (Iraqi Journal of Pharmaceutical Sciences, 2025)
Lornoxicam (LOX) is (NSAID); it is a crystalline powder that ranges in color from orange to yellow and is practically insoluble in water. The aim of this study is to increase the solubility and dissolution of LOX using the surface solid dispersions SSD approach by employing hydrophilic-water insoluble carriers, such as Aerosil 200, Croscarmellose Sodium (CCS), Sodium Starch Glycolate (SSG), Crospovidone and Avicel® PH101. To determine the best drug-carrier interaction, the SSD formulations of LOX were preparing by kneading in various drug: carrier weight ratios (1:1, 1:3, 1:5). They were then assessed for their yield, content of drug, solubility in water, in-vitro release in 7.4 phosphate buffer saline, powder X-ray diffraction, and Fourier Transform Infrared Spectroscopy (FTIR). Most of the prepared SSD formulae demonstrated increased drug solubility. Crospovidone had the most significant results, with a high percentage of yield (98%), high drug content (95.2%), and a 147.6-fold increase in solubility over pure drug solubility with an enhanced dissolution rate. Lornoxicam was transformed into an amorphous form absence of any chemical interaction with the carrier. Therefore, SSD technology successfully increased the solubility and the dissolution rate of LOX.